ANALISIS SISTEM PENGENDALIAN INTERNAL (SPI) TERHADAP SISTEM AKUNTANSI PEMBERIAN KREDIT MODAL KERJA PADA PT. BANK SULUTGO CABANG PEMBANTU SAM RATULANGI - Sondakh, Margareth; Ilat, Ventje; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
In carrying out a credit product, especially working capital credit at a particular bank, there is an accounting system used to process data so that it can obtain financial information needed by the parties concerned. Therefore, to minimize the occurrence of errors and fraud in an accounting system for working capital credit, a good and adequate internal control system is needed. The internal control system is a system that greatly influences the success of the company in carrying out its policies. Therefore, it is necessary to have a system of internal control, especially with respect to the accounting system in providing working capital loans to reduce fraud that will result in losses to the company. This study aims to analyze how the internal control system of the accounting system in providing working capital loans at PT. Bank SulutGo especially in the Sam Ratulangi support branch. The method used is descriptive qualitative. And the results show that PT. Bank SulutGo's Sam Ratulangi subsidiary branch has implemented internal control components well and adequately. And supported by policies and procedures for providing good working capital loans that are also applied by the company.Keywords: Accounting system, internal control system, and working capital credit